EVAPOTRANSPIRATION AND ENERGY BALANCE OF PADDY FIELD AND TEAK PLANTATION - Tongdeenok, Piyapong; Boonyawat, Samakkee (วารสารวนศาสตร์ไทย, 2022)
The objectives of this study are to compare the evapotranspiration (ETa) and energy balance of paddy field and teak plantation and to develop regression models using simple climatic factors for estimation of evapotranspiration in paddy field and teak plantation. The automatic weather station (AWS) data observed at paddy field and teak plantation in Sukhothai and Lampang provinces collected between January 2002 – September 2004 were applied in this study. The results shown that the daily average solar radiation (Rs) in paddy field was 19.3 MJ m-2 day-1 with Rn of 13.2 MJ m-2 day-1 (70.4 % of Rs). The Rn was used for latent heat (LE), sensible heat (H), and storage in soil and water (Gs and Gw) with the average value of 9.5, 3.0, 0.4 and 0.2 MJ m-2 day-1 or 72.3, 2.9, 3.1 and 1.7% of Rn respectively. In teak plantation, the daily average Rs was estimated at 19.0 MJ m-2 day-1 ,. with an avergae daily Rn of 14.8 MJ m-2 day-1 or 78.2% of Rs. The Rn was used for LE, H and Gs about 71.6, 23.0 and 5.4% of Rn respectively. The average daily ETa of the whole peroid study in paddy field was 4.1 mm. while the average daily ETa of teak plantation was 3.9 mm. Regarding estimation of ETa based on general climatic factors using regression model, the most suitable model for paddy field was by found the highest correlation equation in December with r2 = 0.86, while in teak plantation the highest correlation with r2 = 0.84 was found in November. It can be said that the relationship between ETa and micrometeorological data was not applicable for almost all monthly periods. Only some month showed the significant relationship. It is thus recommended that there should be no more use the meteorological data to develop model for prediction ETa.